(untitled) (Fiep Bulletin - online, 2014)
The objective of this descriptive article is to verify the effects of the relative age in the formation of the participating teams in the pan-american games, held in Rio de Janeiro, Brazil, in the year of 2007. The used data in this research is the Pan- American Games registration form of all athletes, found in the main website of the event: . All 222 enrolled athletes of the 12 teams involved in the competition, were divided in two groups: First semester (born between 1st of january and june 30rd) and Second semester (born between july 1st and december 31st). The software SPSS 13.0 was used for the analysis of the data. Binomial with “test proportion” established in 0,50 with p0,05 was used for non-parametric tests. Of the 222 athletes, 150 (68%) were classified in the “first semester” group and 72 (32%) were classified in the “second semester group”, with a p = 0,000. The equatorian team, 1st place in the competition (p = 0,815) and the jamaican team, 2nd place (p = 0,238) didnt showed a significant relative age effect. However, the Bolivian and Argentinan teams, that didnt had a impressive perfomance in the competition, both had an significant relative age effect (p=0,008). In this case, concludes that the relative age effect is not associated with the team’s final perfomance in the Pan-American games, therefore the only 2 teams that had a significant relative age effect did not made the final games, even considering that all the analysed teams the number of athletes born in the firts semester prevailed.